Amnioinfusions to Treat Early Onset Anhydramnios Caused by Bilateral Renal Agenesis : Potter’s Syndrome - Yusrawati Yusrawati; Rizka Fadhillah Yusra (Andalas Obstetrics And Gynecology Journal, 2022)
Introduction: Anhydramnios is a very small amount of amniotic fluid where the MVP measurement is 2cm by ultrasound. The most common cause of anhydramnios that persists into the second trimester of pregnancy is bilateral renal agenesis. Bilateral renal agenesis is closely related to Potter's Syndrome. Potter's syndrome is a picture of reduced amniotic fluid regardless of the cause. The most common cause of newborn death in cases of anhydramnios is pulmonary hypoplasia. Amnioinfusion is an action of adding fluid into the amniotic cavity which is expected to reduce uterine pressure due to anhydramnios and maintain alveolar distension to increase fetal lung growth.Objective: The aim of this case report is to share amnioinfusion on anhydramnios.Case Report: A 26-year-old woman G3P1A1H1 gravid 27-28 weeks was referred to the fetomaternal polyclinic of RSUP M. Djamil Padang with suspicion of anhydramnios caused by bilateral renal agenesis. Physical and obstetric examinations were found to be within normal limits. On ultrasound examination, there was no amniotic fluid, so MVP was difficult to assess, no fetal kidney and bladder were seen, so it is suspected that this is a bilateral renal agenesis disorder and leads to Potter's Syndrome. The patient was subjected to amnioinfusion to prevent contractures and pulmonary hypoplasia in the fetus. From the first amnioinfusion, the MVP increased to 2.99 cm. Monitoring and amnioinfusion are carried out periodically until the fetus is viable to be bornConclusion: Amnioinfusion in bilateral renal agenesis is useful for assisting diagnosis and as a preventive therapy for pulmonary contractures and hypoplasia in the fetus as well as increasing life expectancy when the fetus is born.Keywords: Bilateral Renal Agenesis, Anhydramnios, Amnioinfusion, Potter's Syndrome